PREVALENCE OF GASTROINTESTINAL NEMATODE INFECTION IN LAYERS IN PENINJOAN VILLAGE, TEMBUKU DISTRICT, BANGLI REGENCY, BALI - Belo, Agostinho Moreira; Suratma, I Nyoman Adi; Oka, Ida Bagus Made (Buletin Veteriner Udayana, 2022)
Nematodes are among the most important class of worm parasites in poultry in terms of the number of species and the damage they cause. Common nematode worms that infect the digestive tract of chickens include: Capilaria spp, Tetrameres spp, Aquaria spp, Ascaridia galli, Strongyloides avium , and Heterakis gallinarum . Risk factors that influence the incidence of parasite infection are influenced by; host, parasites and environment. Host factors that most commonly affect the incidence of infection include: type, age, sex, while parasite factors that affect infection include: mode of transmission, viability (survival), pathogenicity and immunogenicity, as well as environmental factors that influence, especially: weather, enclosure sanitation and humidity. The purpose of this study was to determine the prevalence of nematode grastrointestinal infection in laying hens in Tembuku Sub-district, Bangli District, Bali. The object of this study is feces from laying hens taken directly as many as 240 laying hens. The inspection method used is qualitatively using the floating method. The result showed that the prevalence of gastrointestinal nematode worm infection in laying hens was 9,17 %. The result of the data analysis showed that there was no relationship between the age of the laying hens and the prevalence of gastrointestinal nematode worn infection in laying hens reared in Peninjoan village, Tembuku Sub-district, Bangli district, Bali.